Upgrading of micro algal derived bio-fuels in thermochemical liquefaction path and its perspectives: A review. (April 2017) - Arvindnarayan, Sundaram; Sivagnana Prabhu, Kandasamy K.; Shobana, Sutha; Kumar, Gopalakrishnan; Dharmaraja, Jeyaprakash
Abstract: Micro algae are promising attractive energy carriers. Their biomass productivity is 5–30 times higher than that of first and second generation biomass. Additionally, they utilize CO2 for their photosynthetic process thereby protects possibly the environment and contributes towards CO2 remediation at higher rates. Their cultivation can be combined with wastewater and industrial effluents which consequently leads to the bioremediation of inorganic elements more effectively. Among the conversion technologies for the biofuel production from the micro algal biomass, thermochemical conversion is an enduring sustainable alternative path in the view of engineering as this process utilizes all kinds of the biochemical moieties from the micro algal biomass cellular constitution. This article reviews the bio moieties of micro algal biomass, and subsequent use of them in thermochemical liquefaction (TCL) technologies like pyrolysis and hydrothermal liquefaction (HTL) for the extraction of liquid fuels and upgrading of bio-oil processes via decarbonylation, decarboxylation (DCO) and hydrogenation for palmitic/oleic using suitable catalysts viz activated carbon with noble metals & cost-effective tungsten based catalysts. These two technically feasible processes in an appropriate technical downstream path are dependent on the oil upgrading process. Moreover, a comparative study of pyrolysis and HTL processes has been evaluated towards the challenges and opportunities of a commercial-scale microalgae-to-fuels process in the consideration for mitigating technical, environmental, and logistical concern. Highlights: Upgrading of microalgal derived biofuel is reviewed. Thermochemical liquefaction path and its perspectives are discussed. Biomoeities of algal biomass and their utilization has been proposed. New analytical techniques should be explored to evaluate biomoeities of algal biomass.